Salvia miltiorrhiza in osteoporosis: a review of its phytochemistry, traditional clinical uses and preclinical studies (2014–2024) - Wang, Lili; Wang, Shan; Dai, Xuan; Yue, Gaiyue; Yin, Jiyuan; Xu, Tianshu; Shi, Hanfen; Liu, Tianyuan; Jia, Zhanhong; Brömme, Dieter; Zhang, Shuofeng; Zhang, Dongwei (Frontiers in Pharmacology, 2024)
Osteoporosis becomes a global public health concern due to its rising prevalence and substantial impact on life quality. Salvia miltiorrhiza Bunge (Salviae Miltiorrhizae Radix et Rhizoma, SM) has been firstly recorded in Shen Nong's Herbal Classic, and is frequently prescribed in conjunction with other herbs for the management of osteoporosis. This systematic review aims to comprehensively analyze the recent advances of SM on osteoporosis in traditional Chinese clinical uses and preclinical investigations. Literatures encompassing pertinent studies were systematically retrieved across menopaused; Nox4, NADPH oxidase 4; Nrf2, nuclear factor erythroid 2-related factor 2; OCN, osteocalcin; OPG, osteoprotegerin; OPN, osteopontin; Osx, Osterix; OVX, ovariectomized; PINP, procollagen type I N-propeptide; PPARγ, peroxisome proliferator-activated receptor γ; RANK, activator of nuclear factor kappa-Β ligand; RANKL, receptor activator of nuclear factor kappa-Β ligand;